Governing the salmon farming industry: Comparison between national regulations and the ASC salmon standard. (August 2019) - Luthman, O.; Jonell, M.; Troell, M.
Abstract: Farmed salmon has become an important export commodity for many countries and regions. The expanding salmon aquaculture industry has, due to its rapid increase, resulted in environmental concerns, most notably relating to the interaction with wildlife, effects of effluents and discharges in local ecosystems, in some regions overuse of antibiotics and development of Antimicrobial Resistance (AMR) and high dependence on fish resources in feeds. As a response to these concerns, the industry has strengthened their efforts to improve practices and private led sustainability initiatives, including certification and eco-labelling, has become increasingly important. This study examines the differences between salmon farming governance policies in the four largest salmon producing regions; Norway, Chile, Scotland (UK) and British Columbia (Canada) and the Aquaculture Stewardship Council's (ASC) salmon standard. The purpose of the study is to clarify how the standard from a well-established eco-certification program compares to national or regional conventional standards, using additionality as measuring method. The paper concludes that at present the ASC standard has mainly three strong advantages over existing regional/national standards and these relate to; escape numbers allowed, antibiotic usage and fish resources in feed. Changing these three main divergences in the national/regional regulations would significantly improve some of the main sustainability issues with uncertified salmon farming. The study also finds that the potential additionality of the ASC standard can differ between regions, with the highest difference in Chile and lowest in Norway.